A Case of Acute Disseminated Histoplasmosis of the Liver in a Patient Receiving Amphotericin-B Therapy. (9th November 2022) - Irfan, A; Hamdan, H
Abstract: Introduction/Objective: Acute disseminated histoplasmosis (DH), caused by Histoplasma Capsulatum (HC), occurs primarily in immunocompromised hosts. It is characterized by an abrupt onset of symptoms (fever, malaise, hepatosplenomegaly, lymphadenopathy, anemia, leucopenia and thrombocytopenia) and a lack of granulomatous inflammatory response. If left untreated, death occurs within three months of the disease. The treatment of choice is a two-week course of Amphotericin-B (AmpB-Tx). Studies show a drop in fungal load in 85% of blood cultures and a drop of 1.6 U and 2.1 U in serum and urine antigen levels of histoplasmosis respectively, within 14 days of treatment thereby making it unlikely to see liver failure secondary to acute DH in a patient receiving AmpB-Tx. Methods/Case Report: We present a case of a 41-year-old male, newly diagnosed with HIV (CD4=44; viral load=5, 350, 000) and DH on AmpB-Tx. At presentation, his liver function tests (LFT's) were mildly elevated (Bilirubin =2.7mg/dL; ALP=259U/L; AST=271U/L; ALT=71U/L). On Day-9 of AmpB-Tx, he became somnolent and jaundiced with hepatosplenomegaly and ascites. His LFTs were markedly raised, showing an obstructive pattern (Bilirubin=16mg/dL; ALP=1578U/L; AST=261U/L; ALT=213U/L). On Day-11 of treatment, we received a liver biopsy for HIV cholangiopathy versus drug induced hepatotoxicity. The clinicians considered DH to be a less likely cause since the patient was already on AmpB-Tx. The liver biopsy showed hepatocytes with cholestasis, minimal acute portal inflammation and numerous portal tract and parenchymal macrophages laden with fungal organisms. Gomori-Methenamine-Silver stain confirmed the fungal organisms as being HC. This diagnosis prompted the continuation of AmpB-Tx past 14 days. The patient's LFT's reached maximum values of Bilirubin=18mg/dL; ALP=1680U/L; AST=355U/L; ALT=324U/L. After 25 days of AmpB-Tx, his LFT's trended downwards with a resolution of his hepatic encephalopathy and jaundice. While a 14 day course was initially intended, AmpB-Tx was continued for a total of 28 days until a resolution of symptoms was achieved. Results (if a Case Study enter NA): NA. Conclusion: Our case identifies a patient with progressive hepatic histoplasmosis in spite of AmpB-Tx. Keeping in mind and identifying such cases on pathology can alter the course of treatment for patients.